KEPUASAN KERJA SEBAGAI FAKTOR TERBENTUKNYA SIKAP KERJA PEGAWAI NEGERI SIPIL KANTOR KECAMATAN KLAMPIS, BANGKALAN - Arisandi Tri Hardiansyah; Aisyah Amelia; Mila Santika (Universitas Trunojoyo Madura, 2018)
ABSTRACTThis article aims to determine the relationship between organizational job satisfaction which can determine the work attitude of civil servant in the Klampis sub-district office. We conduct interviews by drawing conclusions based on qualitative data and using our perception as authors of every answer that employees provide to us. Out of the total 17 employees, we managed to get answers from 5 employees (due to the limited time) which we were able to use it as a race to determine the level of employee job satisfaction. So that it may not have a big impact for the readers, but can provide information for consideration.